Bank Health Evaluation By Bank Indonesia and Earning Management in Banking Industry - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Many cases and researches show that financial statement usage (that encompasses inherent weaknesses, like flexibility in preparing financial statement) in many businesses contracts has stimulated managers to manipulate earning. Accounting that we know is imperfect. We cannot ignore that fact. What we can do is to know the conditions that can motivate managers to manage earning so they cannot fool us. Paying attention to earning management problems is a contribution in creating trustful information that is useful for efficiency in fund allocation. The objective of this study is to evaluate earning management in banking industry in Indonesia. Is financial statement utilization in bank evaluation (by Bank Indonesia as Central Bank) motivating manager to manage earning? The final sample is 422 financial statement of 244 banks. This sample is classified into three groups based on the delta of bank's healthy score. The empirical results show that Z score of bank's discretionary accrual whose healthy scores decrease (relative to last year score) is positive and significant. Besides that, (-test and ANOVA indicate that discretionary accrual of bank whose healthy scores decrease is higher than discretionary accrual of bank whose healthy scores do not decrease. This implies that bank whose healthy scores decrease make income increasing accrual to hide its under average quality. It is hoped that this study will be useful to all parties that have interest with bank's financial statement, like central bank who has responsibility to monitor banking activities and to regulate banking industry, and users of hank's financial statement, who have interest in fund investments in banking industry. Keywords: banking